Tradisi Berdimbar sebagai Budaya Pernikahan Masyarakat Melayu di Stabat Kabupaten Langkat - Putri Seftrin; Yusra Dewi Siregar (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
In this research there are four focus issues, namely how the process of implementing mandi berdimbar in Langkat Malay traditional weddings, what is the community's view of changes in the mandi berdimbar tradition in Stabat, Langkat Regency, what are the meanings of the mandi berdimbar tradition and how is the development of mandi berdimbar at the moment . The type of method used in this research is a historical research method that goes through four stages, namely heuristics, verification, interpretation and historiography. In collecting data, this research used two methods, namely interviews and documentation. The results obtained from this research are that the mandi berdimbar tradition is a Malay wedding custom from the past. Mandi berdimbar is also called a decorated mandi which is a series of bridal ceremonies which contain a lot of wisdom and teaching. want to get married. Berdimbar bathing is done after the party, the development of the berdimbar tradition is now rarely used, including by Malays, due to the times and the large costs involved in this berdimbar bathing tradition, as well as the lack of time to carry out the berdimbar bathing tradition. In essence, the aim of carrying out the berdimbar bathing event is to teach or remind the bride and groom to carry out the Big Bath (junub) after the wedding night and to convey the joy and gratitude of all the family. In essence, the existence of this tradition must be increased. If it exists among low society, over time this tradition will fade and disappear.